Outcomes of Broader Genomic Profiling in Metastatic Colorectal Cancer: A Portuguese Cohort Study - Ricardo Roque; Rita Santos; Luís Guilherme Santos; Rita Coelho; Isabel Fernandes; Gonçalo Cunha; Marta Gonçalves; Teresa Fraga; Judy Paulo; Nuno Bonito (DNA)
Background: Colorectal cancer (CRC) is the third most diagnosed cancer globally and the second leading cause of cancer-related deaths. Despite advancements, metastatic CRC (mCRC) has a five-year survival rate below 20%. Next-generation sequencing (NGS) is recommended nowadays to guide mCRC treatment; however, its clinical utility when compared with traditional molecular testing in mCRC is debated due to limited survival improvement and cost-effectiveness concerns. Methods: This retrospective study included mCRC patients (≥18 years) treated at a single oncology centre who underwent NGS during treatment planning. Tumour samples were analysed using either a 52-gene Oncomine™ Focus Assay or a 500+-gene Oncomine™ Comprehensive Assay Plus. Variants were classified by clinical significance (ESMO ESCAT) and potential benefit (ESMO-MCBS and OncoKBTM). The Mann–Whitney and Chi square tests were used to compare characteristics of different groups, with significance at p < 0.05. Results: Eighty-six metastatic colorectal cancer (mCRC) patients were analysed, all being MMR proficient. Most cases (73.3%) underwent sequencing at diagnosis of metastatic disease, using primary tumour samples (74.4%) and a focused NGS assay (75.6%). A total of 206 somatic variants were detected in 86.0% of patients, 31.1% of which were classified as clinically significant, predominantly KRAS mutations (76.6%), with G12D and G12V variants as the most frequent. Among 33.7% RAS/BRAF wild-type patients, 65.5% received anti-EGFR therapies. Eleven patients (12.8%) had other actionable variants which were ESCAT level I-II, including four identified as TMB-high, four KRAS G12C, two BRAF V600E, and one HER2 amplification. Four received therapies classified as OncoKbTM level 1–2 and ESMO-MCBS score 4, leading to disease control in three cases. Conclusions: NGS enables the detection of rare variants, supports personalised treatments, and expands therapeutic options. As new drugs emerge and genomic data integration improves, NGS is poised to enhance real-world mCRC management.